Amino acid metabolism genes associated with immunotherapy responses and clinical prognosis of colorectal cancer - Peng, Xinyi; Zheng, Ting; Guo, Yong; Zhu, Ying (Frontiers in Molecular Biosciences, 2022)
Based on amino acid metabolism-related genes (AAMRGs), this study aims at screening out key prognosis-related genes and find the underlying correlation between amino acid metabolism and tumor immune microenvironment of colorectal cancer. Amino acid metabolism-related genes were obtained from MsigDB. The risk signature was built based on differential expression genes, univariate Cox and LASSO analyses with patients’ data downloaded from the TCGA database. Survival analysis and independence tests were performed to confirm the validity of the risk signature. ssGSEA, tumor mutation burden, the score of tumor immune dysfunction and exclusion, the immunophenoscore obtained from The Cancer Immunome Atlas database, and the IC50 of drugs were used to find the relationship between the risk signature, immune status, immunotherapy response, and drug sensitivity of colorectal cancer. We identified 5 amino acid metabolism-related genes for the construction of the risk signature, including ENOPH1, ACAT1, ALDH4A1, FAS, and ASPG. The low-risk group was significantly associated with a better prognosis. We also discovered that the low-risk subgroup was related to more activity of immune cells, higher expression of immune checkpoints, and was more likely to benefit from immunotherapy. To sum up, AAMRGs were associated with the immune microenvironment of CRC patients, and could be applied as biomarkers to predict the prognosis and immunotherapy response of patients.